2006
DOI: 10.1182/blood-2006-09-048686
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor enhances bone tumor growth in mice in an osteoclast-dependent manner

Abstract: Inhibition of osteoclast (OC) activity has been associated with decreased tumor growth in bone in animal models. Increased recognition of factors that promote osteoclastic bone resorption in cancer patients led us to investigate whether increased OC activation could enhance tumor growth in bone. Granulocyte colony-stimulating factor (G-CSF) is used to treat chemotherapy-induced neutropenia, but is also associated with increased markers of OC activity and decreased bone mineral density (BMD). We used G-CSF as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
83
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 46 publications
9
83
0
Order By: Relevance
“…In addition to TNF-α (Azuma et al 2000), IL-1α (Jimi et al 1999), IL-6 (Kudo et al 2003), monocyte chemoattractant protein-1 (MCP-1; Lu et al 2007), macrophage inflammatory protein-1 alpha (MIP-1α; Lee et al 2007), and granulocyte colony-stimulating factor (G-CSF; Hirbe et al 2007), which have all recently been shown to promote Oc formation, we have also identified IL-10, IL-12p70, IL-9, leptin, and Regulated upon Activation, Normal T cell expressed, and secreted (RANTES) as highly expressed cytokines in pOcs undergoing P. aeruginosa LPS-mediated Oc formation.…”
Section: P Aeruginosa Lps-mediated Osteoclast Formation In Monocultumentioning
confidence: 99%
“…In addition to TNF-α (Azuma et al 2000), IL-1α (Jimi et al 1999), IL-6 (Kudo et al 2003), monocyte chemoattractant protein-1 (MCP-1; Lu et al 2007), macrophage inflammatory protein-1 alpha (MIP-1α; Lee et al 2007), and granulocyte colony-stimulating factor (G-CSF; Hirbe et al 2007), which have all recently been shown to promote Oc formation, we have also identified IL-10, IL-12p70, IL-9, leptin, and Regulated upon Activation, Normal T cell expressed, and secreted (RANTES) as highly expressed cytokines in pOcs undergoing P. aeruginosa LPS-mediated Oc formation.…”
Section: P Aeruginosa Lps-mediated Osteoclast Formation In Monocultumentioning
confidence: 99%
“…Conversely, AMD3100 -which does not mobilize HSCs by activating osteoclastogenesis, but rather by interfering directly with CXCR4/CXCL12 bindingdid not active osteoclasts to mobilize PCa cells, as predicted (Supplemental Figure 6, J and K; and ref. 27). Together, these data suggest that disseminated PCa cells compete with HSCs for the niche using the same molecular mechanisms as do HSCs to gain access and egress of the niche (e.g., CXCR4/CXCL12).…”
Section: Figurementioning
confidence: 99%
“…Several studies previously showed that G-CSF promotes osteopenia, 51,52 and transgenic mice encoding human G-CSF developed osteoporosis with increased osteoclast activity. 53 Consistently, mononuclear cells from G-CSF-mobilized blood showed higher osteoclast differentiation potential than those isolated from healthy controls, 54 and G-CSF augments osteoclast formation in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…53 Consistently, mononuclear cells from G-CSF-mobilized blood showed higher osteoclast differentiation potential than those isolated from healthy controls, 54 and G-CSF augments osteoclast formation in vitro. 51 Moreover, G-CSF treatment can exacerbate arthritis, and rheumatoid arthritis is associated with elevated serum G-CSF levels, 55 whereas G-CSF receptor-deficient mice are refractory to collagen-induced arthritis. 56 Of note, arthritis patients contain increased percentages of activated neutrophils, and these cells may represent a major reservoir of osteoclasts in psoriatic arthritis patients.…”
Section: Discussionmentioning
confidence: 99%